The Analysis of the English Use and Barriers in Front Office in Hotels in Bali - Ariyati, Kadek Feni (e-Journal of Linguistics; Vol 16 No 2 (2022): ejl-JulyDO - 10.24843/e-jl.2022.v16.i02.p08, 2022)
Communication is an essential element of the hospitality industry. Spoken and written communication skill is important for all hoteliers. The most important is the English skill. The significance of English skills from front office staff at hotels in Bali is a specific perception case occurring in the hospitality industry. In this case, communication skills, language skills, the willingness to understand guests' interests, and showing politeness are the leading factors in improving the quality of service. This study aimed at analyzing the function and obstacles in using English by the front office staff at hotels in Bali. Data were collected through depth interviews with the hotel front office staff. The results show that English plays an essential role in the front office for greeting and welcoming, registering, handling check-in and check-out, providing information, diplomatic agent, and problem solver. The obstacles faced in using English happening in the front office department should be minimized by providing special training to the staff. Besides, the obstacle in using English can also be solved by the collaboration between the government and educational institutions focusing on tourism study to graduate qualified students who are ready to face the real work practice and be the ones with excellent communication skills.